IMPLEMENTASI E-GOVERNMENT ICORE DALAM PENINGKATKAN PELAYANAN PUBLIK DI KABUPATEN PANGKEP - AR, Mutia Islam; Malik, Ihyani; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the implementation of e-government icore in improving public services at the Department of Population and Civil Registration in Pangkep district. The type of research used is qualitative research with descriptive research type. Data collection techniques include observation, interviews, and documentation. The results of the study are 1) Elements of Support, Support or support provided by the Government regarding the development of e-government implementation of the icore application is said to be optimal and has received great support since the official launch of the icore application. 2) Elements of Capacity (capacity), Capacity or capacity regarding resources both in terms of financial, infrastructure and human in the implementation of e-government icore in improving public services at the Pangkep Regency Population and Civil Registration Office has been considered optimal. Related to the availability of financial or budgetary resources, this comes from the APBD 3) Elements of Value (benefits) The value or benefits of the icore application have been felt by the community with the various kinds of conveniences offered,